Evolution of Dementia Related to the Use of Alcohol in the French Nationwide Discharge Summary Database Between 2007 and 2017. Issue 3 (May 2019) - Rochoy, Michaël; Gautier, Sophie; Béné, Johana; Bordet, Régis; Chazard, Emmanuel
Background: The French nationwide exhaustive hospital discharge database (PMSI) is used for activity-based payment of hospital services. We hypothesized that the release of articles about alcohol and dementia could influence the identification of these diagnoses in PMSI. Methods: We analyzed temporal evolution of coding for dementia and other persistent or late-onset cognitive impairment (OPLOCI) due to alcohol and other psychoactive substances in the PMSI database from 2007 to 2017 (285 748 938 inpatient stays). These codings use the International Classification of Diseases, 10th revision (ICD-10). Results: The number of inpatient stays with dementia and OPLOCI due to alcohol increased from 34 to 1704 from 2007 to 2017. While the number of diagnosed dementias remained stable at around 400 from 2013, the number of OPLOCIs increased 10-fold from 2013 to 2017. This increase was not found with dementia or OPLOCI due to other psychoactive substances than alcohol. Conclusion: Notoriety of a diagnosis in the literature seems to have an impact on the coding.